2016
DOI: 10.1016/j.ydbio.2016.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Cell death regulates muscle fiber number

Abstract: Cell death can have both cell autonomous and non-autonomous roles in normal development. Previous studies have shown that the central cell death regulators grim and reaper are required for the developmentally important elimination of stem cells and neurons in the developing central nervous system (CNS). Here we show that cell death in the nervous system is also required for normal muscle development. In the absence of grim and reaper, there is an increase in the number of fibers in the ventral abdominal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…It has previously been shown that the nervous system is required for the establishment of the adult muscle pattern (Currie and Bate, 1995) and that motor axons serve as a support for migration of AMPs during larval and pupal development (Currie and Bate, 1991). More recently, it has also been suggested that the nervous system could be involved in the selection of founder cells from the pool of AMPs (Sarkissian et al, 2016). Here, we took advantage of a previously described genetic context ( pan-muscular expression of NetB) to affect the SNa (Winberg et al, 1998) and test impact of SNa loss on L-AMPs.…”
Section: The Sna Is Required For Maintenance Of Associated L-amps At mentioning
confidence: 99%
“…It has previously been shown that the nervous system is required for the establishment of the adult muscle pattern (Currie and Bate, 1995) and that motor axons serve as a support for migration of AMPs during larval and pupal development (Currie and Bate, 1991). More recently, it has also been suggested that the nervous system could be involved in the selection of founder cells from the pool of AMPs (Sarkissian et al, 2016). Here, we took advantage of a previously described genetic context ( pan-muscular expression of NetB) to affect the SNa (Winberg et al, 1998) and test impact of SNa loss on L-AMPs.…”
Section: The Sna Is Required For Maintenance Of Associated L-amps At mentioning
confidence: 99%
“… Emori and Saigo (1993) analyzed the expression of the two FGF receptor genes during development and showed that heartless (htl) , but not breathless , was expressed in the wing disc associated myoblasts. Moreover, previous studies highlighted the role of Heartless in the specification of founder cell and regulation of fiber number during adult abdominal myogenesis ( Dutta et al, 2005 ), and FGF ligands regulate the number of adult abdominal muscles ( Sarkissian et al, 2016 ). Furthermore, Htl signaling controls the number of leg disc associated myoblasts and activates one of the Wingless targets, ladybird , to regulate fiber formation ( Maqbool et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%